(untitled) - Picot, Andre (New York, N.Y.,Cambridge, 1995)
This includes adequate knowledge concerning dangerous substances and intermediates that may be formed and which can determine the stability and toxicity of mixtures; the risks inherent to certain reactions and manipulations,...
Keywords: Chemical laboratories,Thí nghiệm hóa học; Safety measures,Mức độ an toàn